Effect of carbamide peroxide-based bleaching agents containing fluoride or calcium on tensile strength of human enamel Efeito de agentes clareadores à base de peróxido de carbamida contendo fluoreto e cálcio na resistência à tração do esmalte humano - Marcelo Giannini; Alessandra Peres Silva; Vanessa Cavalli; Adriana Franco Paes Leme (University of São Paulo, 2006)
OBJECTIVE: The aim of this study was to evaluate the effects of carbamide peroxide-based bleaching agents (CPG) containing fluoride (CF) or calcium (CCa) on the ultimate tensile strength of enamel (UTS). METHOD: A "cube-like" resin composite structure was built-up on the occlusal surface of twenty-two sound third molars to facilitate specimen preparation for the micro-tensile test. The restored teeth were serially sectioned in buccal-lingual direction in slices with approximate 0.7 mm thickness. Each slice was trimmed with a fine diamond bur to reduce the buccal, internal slope enamel of the cusps to a dumb-bell shape with a cross-sectional area at the "neck" of less than 0.5 mm². The samples were randomly divided into 12 groups (n=11). The control groups were not submitted to the bleaching regimen. Specimens were treated with 10% CPG gel or with 10% CPG formulations containing CF (0.2% and 0.5%) or CCa (0.05% and 0.2%). Bleached groups received the application of the 10% CPGs for 6 hours/day at 37º C, during 14 consecutive days and were stored in artificial saliva (AS) or 100% relative humidity (RH) among each application. After bleaching, specimens were tested with the microtensile method at 0.5 mm/min. Data were analyzed by two-way ANOVA and Tukey test (5%). RESULTS: No significant difference was observed between groups stored in AS or RH. Specimens treated with CF or CCa presented similar UTS as unbleached control groups. CONCLUSION: Either 10% CPG formulations containing CF or CCa can preserve the UTS after bleaching regimen. OBJETIVO: O propósito deste estudo foi avaliar os efeitos de agents clareadores à base de peróxido de carbamida (CPG) contendo fluoreto (CF) e cálcio (CCa) na resistência à tração do esmalte (UTS). MÉTODO: Um bloco de resina composta foi confeccionada na superfície oclusal de vinte e dois terceiros molars hígidos para facilitar a preparação dos espécimes para o teste de micro-tração. Os dentes restaurados foram seccionados com disco diamantado no sentido vestíbulo-lingual em fatias de aproximadamente 0,7 mm de espessura. Com uma ponta diamantada, foi realizada uma constrição na região de esmalte da vertente oclusal interna. Os espécimes apresentaram aproximadamente 0,5 mm² de área na secção transversal da região de constrição e foram divididos em 12 grupos (n=11). Os grupos controles não foram submetidos ao regime clareador e os experimentais foram tratados com gel de CPG 10% ou com formulações de CPG 10% contendo CF (0,2% e 0,5%) ou CCa (0,05% e 0,2%). Os grupos clareadores receberam a aplicação dos CPGs por 6 horas/dia a 37ºC, durante 14 dias consecutivos e foram armazenados em saliva artificial (AS) ou em umidade relativa 100% (RH), entre as aplicações do gel clareador. Após o clareamento, os espécimes foram testados através do método de micro-tração (0,5 mm/min). Os dados foram analisados pela ANOVA (2 fatores) e teste Tukey (5%). RESULTADOS: Nenhuma diferença foi observada entre os grupos armazenados em AS ou RH. Os espécimes tratados com CPG com CF ou Cca apresentaram similar UTS aos grupos controles não clareados. CONCLUSÃO: Ambos CPGs 10% CF or CCa não alteraram a UTS após o tratamento clareador.